The Effect of Situational Leadership Style on the Performance of Sales Representatives - Falih Suaedi, Koen Irianto Uripan, (Opción, 2019)
The purpose of this study was to identify simultaneous and partial influence between situational leadership style and motivation on the performance of sales representative in PT. Luxindo Raya Surabaya. This study was an explanatory study using a statistical test. The findings of this study indicate that theories of leadership style with behavioral approach oriented to maturity and wide views on the task, motivation, need-for-achievement, and ability to establish relationships will be able to improve one’s performance. In conclusion, in situational leadership, it is important for every leader to make a good diagnosis of the situation.